Resale Price Maintenance: Hurting Competitors, Consumers and Yourself - Matthias Hunold; Johannes Muthers (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
Improving retailers' incentives for service is a prominent efficiency defense for resale price maintenance (RPM). We investigate the incentives of symmetric manufacturers to use RPM when selling products through common retailers who provide services such as pre-sale advice. We show that the possibility to use minimum RPM can create a dilemma for manufacturers when retailers influence consumer choice through service. If price competition among retailers is strong, a manufacturer benefits from introducing minimum RPM as it incentivizes retailers to favor the sales of her product. However, other manufacturers follow into RPM. In the symmetric equilibrium, service is unbiased, but retail margins and consumer prices are higher than without RPM. In turn, manufacturers' profits and social welfare are lower. This challenges the service argument as an efficiency defense for RPM.
Keywords: D83; L42; 330; biased sales advice; common agency; manufacturer dilemma; matching; RPM; vertical restraints; Preisbindung; Konsumgüterindustrie; Einzelhandel; Dienstleistung; Bias; Wettbewerb; Wohlfahrtsanalyse; Theorie